PENGARUH DAYA ANTIBAKTERI EKSTRAK ETANOLIK BUNGA KAMBOJA PUTIH (Plumeria alba) TERHADAP PERTUMBUHAN BAKTERI PLAK GIGI Aggregatibacter actinomycetemcomitans (Kajian secara In Vitro) - , ADIBAH MAULANI; , drg. Prayitno, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2013)
White frangipani (Plumeria alba) has long been used traditionally to cure some diseases in Indonesia because of their therapeutic properties. Recent studies show that extract of Plumeria alba flowers contain alkaloid, tannin, flavonoid, steroid, saponin, and terpenoid that possess antibacterial activity. Aggregatibacter actinomycetemcomitans is gram negative facultative anaerobic microorganism which is normally found in dental plaque. The goal of this study was to determine the antibacterial activity of Plumeria alba etanolic extract in inhibiting Aggregatibacter actinomycetemcommitans growth. This study had been done using 20%, 40%, 60%, and 80% concentration of Plumeria alba extract and also sterile aquadest as the negative control. The organisms were cultured in 5 plates of Mueller Hinton Agar and the test carried out on it. This antibacterial test used well-diffusion method with 5 samples for each concentration. The plates were incubated at 370C for 24 hours. Microbial growth was determined by measuring the zone of inhibiton. The result was analyzed by using One Way Anova and Post Hoc LSD. The result showed that Plumeria alba etanolic extract has antibacterial activity in inhibiting Aggregatibacter actinomycetemcommitans (P<0,05). This antibacterial activity had significant difference in 20%, 40%, and 60%.